Characterization in Ancient Greek Literature Studies in Ancient Greek Narrative, vol. 4 - De Temmerman, Koen; van Emde Boas, Evert (Mnemosyne, Supplements, 2018)
This is the fourth volume in the series Studies in Ancient Greek Narrative. The book deals with the narratological concepts of character and characterization and explores the textual devices used for purposes of characterization by ancient Greek authors from Homer to Heliodorus.; Readership: Anyone working on ancient Greek (narrative) literature, and anyone interested in issues of character and characterization in both ancient and modern literature.